Changes in the number of intensive care unit beds in US hospitals during the early months of the coronavirus disease 2019 (COVID-19) pandemic. (3rd October 2022) - Weiner-Lastinger, Lindsey M.; Dudeck, Margaret A.; Allen-Bridson, Katherine; Dantes, Raymund; Gross, Cindy; Nkwata, Allan; Tejedor, Sheri Chernetsky; Pollock, Daniel; Benin, Andrea
Abstract: Using data from the National Healthcare Safety Network (NHSN), we assessed changes to intensive care unit (ICU) bed capacity during the early months of the COVID-19 pandemic. Changes in capacity varied by hospital type and size. ICU beds increased by 36%, highlighting the pressure placed on hospitals during the pandemic.